42.3k views
5 votes
Anyone know what the answer is???(sorry if it’s unclear)

Anyone know what the answer is???(sorry if it’s unclear)-example-1
User Bokor
by
5.4k points

1 Answer

1 vote

The laws of exponents I will be using are:


(x^y)^z = x^(yz), and
x^y \cdot x^z = x^(y+z).

For the first part,
(15^3)^3 \cdot 15^(-6) = 15^9 \cdot 15^(-6) = 15^3.

For the second part,
15 \cdot (15^3)^2 \cdot (15^(-5))^2 = 15 \cdot (15^6) \cdot (15^(-10)) = 15^(1+6-10) = 15^(-3) = (1)/(15^3).

User NewPersona
by
5.4k points